The economics and politics of foreign aid and domestic revenue - Abrams M. E. Tagem (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
The main argument of this paper is that there is considerable heterogeneity in the way aid can shape tax performance in developing countries: through behavioural effects, donor conditionality, recipient policy reform and technical assistance; and these effects are country-specific. We investigate these effects by applying the dynamic Common Correlated Effects Mean Group estimator to a dataset comprising 84 developing countries from 1980 to 2013. The following results ensued: aid and taxes comprise an equilibrium relation, with a positive long-run association between aid and taxes; causality runs from aid to taxes, suggesting that on average, changes in aid induce permanent changes in taxes.
Keywords: C23; E62; F35; O23; 330; aid; taxation; tax reform; cointegration; common factor models